Development of scientific competences in students of basic secondary and secondary education as a purpose of pedagogical management (Revista Estudios Psicológicos, 2022)
This article derives from the research carried out in the official educational institution Centro of Integration Popular IPC of the tourist district of Riohacha, whose objective was to analyze the level of incidence of the pedagogical practices of chemistry in the development of scientific competences of students of basic education secondary. The research design was non-experimental, cross-sectional. For the evaluation of the development of scientific competences, a grid for the evaluation of scientific competences was used from questionnaires of standardized pencil and paper questions designed based on the Saber Icfes census tests. For the analysis of the information, descriptive statistics were used, the results allowed rejecting the working hypothesis, in the sense of affirming that the pedagogical practices of the chemistry area of the educational institution promote in a limited way the pertinent development of scientific competences.
Keywords: teaching; natural sciences; chemistry; scientific training; skills